PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP OPERASI ALJABAR ANAK SPECTRUM AUTIS DENGAN MEDIA VIDEO INTERAKTIF - SUCIATI, DWI WAHYU; Panglipur, Indah Rahayu; Murtinasari, Frida (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
The objective of this study is to enhance the algebraic skills of children on the autism spectrum by employing interactive media. This research introduces a novel approach aimed at boosting the capabilities of children with autism spectrum disorder through the utilization of interactive video media. The study was conducted directly on a 14-year-old child identified as AK, who is in the sixth grade of elementary school and has autism spectrum disorder. Data for this research was gathered through interviews, observations, and documentation methods. The findings of the research indicated a notably limited grasp of algebraic operations concepts among children on the autism spectrum. The underlying cause for this limited understanding was found to be is because appropriate learning media is needed for learning. Subject AK, who is a child on the autism spectrum, experienced an increase in his ability to understand concepts in algebraic operations using interactive video media. Improvement is shown in response, activity, and being able to interact well. This interactive video media was specially created to suit the needs and conditions of AK's initial knowledge of algebraic operations. A follow-up recommendation that can be carried out is to conduct development research on interactive video media specifically for children on the autism spectrum.